CONCEPTUAL BASES OF UKRAINE’S DEFENSE SUFFICIENCY ASSESSMENT - Kopanchuk , V. (Theory and Practice of Public Administration, 2020)
The article deals with the issue of ensuring national security of Ukraine. Today, national security depends to a large extent on the proper defense sufficiency of the state, since military capabilities and its components affect stability in society, the protection of citizens’ rights and freedoms, the rule of law and the preservation of the integrity of the state. Defense sufficiency assessment is an integral part of the state’s defense policy planning process. It envisages finding the optimal balance between the level of guaranteed security of the state’s military security and its economic capabilities. Assessment of the state’s defense sufficiency is carried out using a number of indicators, in particular: reasonable sufficiency of defense, optimal number of armed forces, permissible degree of military-economic tension of the state. The experience of democratic countries shows that military construction policy, as a rule, has a significant impact on civilians. At times, their views differ significantly from those of the military regarding the choice and implementation of defense principles. In particular, this is the case when developing and implementing the Military (Defense) Budget. The main reason for the differences is the complexity and conditions of the task of finding the necessary (in the context of - rational) correlation of national security interests with the structure and capabilities of the armed forces, the military doctrine, the state and prospects of economic development, as well as the coordination of the basic parameters of the military (defense) and state budgets. Therefore, in this case, the key here is the proper level of civilian-military relations and the essence that is embedded in the concept of “defense sufficiency.” It has been found out that public authorities should make efforts to achieve a rational balance of the state’s efforts in the military and non-military spheres. This is the approach that military and civilian experts should put at the heart of developing conceptual approaches to ensuring Ukraine’s defense capability.